Interaction of ozone with formic acid: A system which supresses the scavenging effect of HCO3-/CO32- - (:unkn) unknown (IWA PUBLISHING, 2004)
Formic acid, mainly found in its ionized form at pH values greater than 3.75, is among the major by-products of drinking water ozonation. This study focusses on ozone decomposition reactions when formate ion is present. A mechanistic model was developed for ozone decomposition in the presence of formate ion and alkalinity. n-chlorobutane (BuCl) was used as a hydroxyl radical probe. The proposed mechanism is a combination of all the reactions provided in the literature for ozone decomposition, ozone-formate ion interactions, and formate ion and certain inorganic radical interactions in aqueous solutions. The validity of the proposed mechanism was tested by comparing the experimental data collected at different initial ozone and formate ion concentrations, pH and alkalinity to the model predictions. The model was capable of predicting the ozone decomposition and BuCl oxidation data extremely well when 1.53 M(-1)s(-1) (k(new)) was used as the reaction rate constant for the reaction between ozone and formate ion, as opposed to the value provided in the literature (100 M(-1)s(-1)). Furthermore, according to the proposed model formate ion suppresses the scavenging effect of HCO3- and CO32- ions because the reaction of formate ion with CO3.- radical regenerates the OH. radical that is scavenged by the HCO3- and CO32- ions. This was tested by observing ozone decomposition at different levels of alkalinity in the presence of formate ion. The experimental data did not present any significant effect of alkalinity on the decomposition rate. In addition, the model provided highly reliable predictions of the experimental data collected in the presence of alkalinity when k(new) was used.
Keywords: ozone; formic acid; butyl chloride; hydroxyl radical; carboxyl radical; carbon dioxide radical; modelling; CARBOXYLIC-ACIDS; AQUEOUS-SOLUTION; RATE CONSTANTS; WATER; DECOMPOSITION; OZONATION; RADICALS; REMOVAL